BIOPIC FILM AND POLITICAL IDENTITY: CONTESTATION OF DIVERSITY OF IDEOLOGY IN INDONESIAN MOVIES TEXT POST-SOEHARTO REGIME - Haryanto, Dwi (Capture : Jurnal Seni Media Rekam, 2018)
This discussion examines the textuality relationship between the historical facts of biography and the narrative structure of films that present figures who during the New Order (Orde Baru) regime were alienated from Indonesian historiography. Through a study of the films Gie, Soegija, Sang Kiai, Soekarno, and Jenderal Soedirman, they can deconstruct the meaning of historical films produced by the New Order regime which are dominated by Soeharto's image. The emergence of biopic films that narrate the characters with identity plurality is a deconstructive tipical and reflects the antithesis of filmmakers on film products in the era of the Soeharto regime. Whereas in the New Order era, films with epic historical genre, identical to the hegemony of the military struggle which are reduced by civil society narratives, such as moslem teacher (kiai) and moslem student (santri) and other minority groups, which in the context of historical facts also contributed greatly to the era of nation formation through representation of ethnic nationalism and civic nationalism. The Indonesiandiscourse which is reflected in the hidden meanings of biopic films studied represents a plurality of ideologies and identity political formation in popular culture products.